The Relation between Knowledge on Menopause and Anxiety Facing Menopause in Perimenopausal Women - Insari, Yustina Vitia; Purnamaningsih, Esti Hayu (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to ascertain the relation between knowledge on menopause and anxiety with regards to facing menopause in perimenopausal women. It is hypothesized there is a negative relation between knowledge on menopause and anxiety with regards to facing menopause in perimenopausal women. The subjects in this study are 67 women, ages 40 to 50 years old, in the perimenopausal stage, married, and had never undergone a hysterectomy. All subjects completed two data-gathering instruments: facing-menopause-anxiety scale and knowledge on menopause questionnaire. Simple linear regression was used to analyze the data. The result obtained from this study indicates there is a significant relation between knowledge on menopause and anxiety with regards to facing menopause in perimenopausal women (p